ANALYSIS OF WAITING TIME FOR PATIENT SERVICE USING LEAN CONCEPT IN OUTPATIENT CARE INSTALLATIONS OF STELLA MARIS HOSPITAL, MAKASSAR CITY - Nur Miftahul Janna, Fridawaty Rivai , Indahwaty Sidin, Syahrir A. Pasinringi , Noer Bahry Noor , Yahya Thamrin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
To carry out the functions and duties of the hospital, the hospital provides outpatient services which is one of the services that is the main concern of hospitals throughout the world, because the number of outpatients is much larger than inpatients so that outpatients are a source of market share. which is predicted to offset the income from inpatients in the future which can increase the hospital’s finances. This study aims to analyze the waiting time for patient care using the lean concept in the outpatient installation of Stella Maris Hospital Makassar. The type of research carried out is a mix method by measuring the waiting time for patient services as many as 100 patients and using interview guidelines for 8 informants, namely the head of the outpatient installation (1 person), admission officer (3 people), hospital director (1 person), and nurses ( 3 people) . The results of the interviews were analyzed through data reduction, data presentation, and drawing conclusions. To test the quality of the data, it is done by describing the patient service process in the form of a flowchart. The results of observations showed that there were problems with waiting times, doctors who arrived late, queues for picking up queues that often had problems, rs had not implemented an rs sim. Therefore, hospitals need to interconnect SIMRS in all parts of the hospital, intervene in improvements and continuously evaluate so that the results are more measurable to be used as information in decision making.